1991
DOI: 10.1182/blood.v78.10.2721.bloodjournal78102721
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and monocyte adherence to and migration across monolayers of cytokine-activated endothelial cells: the contribution of CD18, ELAM-1, and VLA-4

Abstract: Pretreatment of endothelial cells with cytokines enhances the adherence of leukocytes, a process that is mediated by surface proteins expressed on both cell types. A three-dimensional model system for the simultaneous determination of leukocyte adherence and migration was used to study the contribution of CD11/CD18, endothelial leukocyte- adhesion molecule-1 (ELAM-1) and VLA-4 in neutrophil and monocyte adherence to and migration through cytokine-activated endothelial cells. Pretreatment of endothelial cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…Furthermore, in contrast to ELAM-I, which modulates both neutrophil and Mo to cytokine-induced ECs, VCAM functions as a ligand for the integrin VLA-4, which is expressed on monocytes but not on neutrophils. Together with these studies, we found that mAbs against VCAM can inhibit Mo adherence to cytokine-induced ECs by up to 40070, whereas other studies showed that ELAM-I mAb can block this process by 30% [19]. Further quantitative blocking studies with respective antibody against molecules on Mos are needed to evaluate tile precise molecule(s) involved in Mo adhesion.…”
Section: Ib Dmentioning
confidence: 56%
See 2 more Smart Citations
“…Furthermore, in contrast to ELAM-I, which modulates both neutrophil and Mo to cytokine-induced ECs, VCAM functions as a ligand for the integrin VLA-4, which is expressed on monocytes but not on neutrophils. Together with these studies, we found that mAbs against VCAM can inhibit Mo adherence to cytokine-induced ECs by up to 40070, whereas other studies showed that ELAM-I mAb can block this process by 30% [19]. Further quantitative blocking studies with respective antibody against molecules on Mos are needed to evaluate tile precise molecule(s) involved in Mo adhesion.…”
Section: Ib Dmentioning
confidence: 56%
“…The functional differences between Mos and other leukocytes might also be due to the differences of surface characteristics [40]. The molecular basis for Mo active movement on and adhesion to 'resting' ECs is not clear, but a likely candidate would be the leukocyte/32 integrin CDI I / C D I 8 complex because CDI I / C D I 8 is largely required for Mo transendothelial migration [19]. Mo-EC interactions can be regulated by a numbe," of factors [4,10,11,30,42,48], among which IL-I and TNF are notorious for their various originality and plurifunction as inflammatory mediators [24].…”
Section: Ib Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary adhesion molecules belonging to the 1 and 2 integrin families achieve a strong attachment and extravasation of leucocytes [3,30]. VCAM-1 and its ligand VLA-4 play an important role in the in vitro adherence of monocytes and activated T cells [31,32] to endothelium. A recent report [33] that interactions between adhesion molecules like VCAM-1 on HEC may play an important role in the perpetuation of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CDI l b on the cell surface is not only indicative for PMN degranulation, but also subserves PMN adhesion to other cells. CDll b belongs to the integrin family of adhesion molecules and is involved in the adherence of PMNs to activated endothelial and epithelial cells by interaction with its counterstructure ICAM-I present on these cells [31,32]. Following adhesion, PMNs transmigrate between the cells and migrate ahmg a gradient of chemoattractant, such as PAF and fMLP.…”
Section: Discussionmentioning
confidence: 99%